FORMATIVE MOVEMENTS IN THE MACHINE WITH "NON-UNITARY" COORDINATION - Isamov Raim Nosimovich; Juraev Jurabek Malikovich (Galaxy International Interdisciplinary Research Journal, 2021)
The article covers methods and schemes for increasing the accuracy of shaping movements by replacing mechanical circuits with electronic circuits of coordinating movements, both between adjustable and stepper drives, and between two adjustable drives.